Memory and the Jesus tradition - Kirk, Alan (New York Bloomsbury T&T Clark, 2018)
Abbreviations -- Preface -- 1. Memory and Media: Towards a New History of the Tradition -- PART ONE: Formation of the Jesus Tradition -- 2. Social and Cultural Memory -- 3. Cultural and Cognitive Approaches to the Gospel Tradition -- 4. The Memory-Tradition Nexus in the Synoptic Tradition:Memory, Media, and Symbolic Representation -- 5. The Formation of the Synoptic Tradition: Cognitive and Cultural Approaches to an Old Problem -- PART TWO: Memory and Manuscript -- 6. Memory and Manuscript: Gerhardsson Revisited -- 7. Manuscript Tradition as a Tertium Quid: Orality and Memory in Scribal Practices -- 8. Memory, Scribal Media, and the Synoptic Problem -- PART THREE: Memory and Historical Jesus Research -- 9. The Memory of Violence and the Death of Jesus in Q -- 10. Memory Theory and Jesus Research -- 11. Cognition, Commemoration, and Tradition: Memory and the Historiography of Jesus Research -- PART FOUR: Memory in 2nd Century Gospel Writing -- 12. The Johannine Jesus in the Gospel of Peter: A Social Memory Approach -- 13. Tradition and Memory in the Gospel of Peter -- Bibliography -- Index of References -- Index of Authors
Alan Kirk argues that memory theory, in its social, cultural, and cognitive dimensions, is able to provide a comprehensive account of the origins and history of the Jesus tradition, one capable of displacing the moribund form-critical model. He shows that memory research gives new leverage on a range of classic problems in gospels, historical Jesus, and Christian origins scholarship. This volume brings together 12 essays published between 2001 and 2016, newly revised for this edition and organized under the rubrics of: 'Memory and the Formation of the Jesus Tradition'; 'Memory and Manuscript'; 'Memory and Historical Jesus Research'; and 'Memory in 2nd Century Gospel Writing'. The introductory essay, written for this volume, argues that the old form critical model, in marginalizing memory, abandoned the one factor actually capable of accounting for the origins of the gospel tradition, its manifestation in oral and written media, and its historical trajectory
Includes bibliographical references and index
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Jesus Christ -- Historicity; Bible -- Criticism, interpretation, etc; Memory; Christianity -- Origin; Recollection (Psychology)